Delivery of antiseptic solutions by a bacterial cellulose wound dressing: Uptake, release and antibacterial efficacy of octenidine and povidone-iodine. Issue 4 (June 2020) - Bernardelli de Mattos, Ives; Nischwitz, Sebastian P.; Tuca, Alexandru-Cristian; Groeber-Becker, Florian; Funk, Martin; Birngruber, Thomas; Mautner, Selma I.; Kamolz, Lars-Peter; Holzer, Judith C.J.
Highlights: BNC is an excellent carrier to create on-demand antiseptic wound dressings. When loading BNC, the formulation has to be considered that might influence uptake and release of the active ingredient. Tested by using FITC-dextran molecules, the uptake and release of molecules into the BNC is size dependent. The uptake and release capacity of BNC makes it a promising carrier for larger molecules. Abstract: Background: Bacterial nanocellulose (BNC) is considered a promising carrier for various substances and novel approaches using BNC in combination with antiseptics are well documented. However, the difference in the molecular weight of these molecules influences their uptake by and release from BNC. Analysing the diffusion of standard molecules with different weight, e.g. dextrans, offers the possibility to investigate the mobility of various molecules. We aimed to test the use of BNC regarding uptake and release of different standard molecules as well as two commercially available antiseptics for possible applications in future wound dressings. Material and methods: Diffusion profiles, uptake and release of three FITC-dextran molecules differing in weight as well as octenidine (Octenisept®) and povidone-iodine (Betaisodona®)-based antiseptics were tested with BNC-based wound dressings. Furthermore, the antiseptic efficacy of BNC in combination with antiseptics against Staphylococcus aureus was tested. Results: Uptake and release capacity for FITC-dextran molecules showed a molecular weight-dependent mobility from BNC into an agarose gel. The loading capacity of BNC was also inversely proportional to the molecular weight of the antiseptics. The release test for octenidine showed a sustained and prolonged delivery into a solid matrix, whereas povidone-iodine was released faster. Both antiseptic solutions combined with BNC showed a good dose-dependent efficacy against S. aureus . Conclusion: Results obtained from the mobility of FITC-dextran molecules in the BNC matrix could open possible applications for the combination of BNC with other molecules for medical applications. Combination of both tested antiseptics with BNC showed to be an efficient approach to control bacterial infections.